2014
DOI: 10.1902/jop.2013.130078
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ, Interleukins‐6 and ‐4, and Factor XIII‐A as Indirect Markers of the Classical and Alternative Macrophage Activation Pathways in Chronic Periodontitis

Abstract: The presence of IFN-γ, IL-6, IL-4, and FXIII-A in healthy individuals and in patients with CP suggests that macrophages may be activated by both classic and alternative pathways in health and in periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…However, there are conflicting reports regarding changes in the M2 phenotype 10,12,14,15 . Some studies found an enhancement of the M2 phenotype in periodontitis, 10 , 12 whereas other studies found a decrease 14 , 15 . In this context, phenotypic switch of macrophage M1/M2 remains uncertain because of the lack of an in situ analysis of the macrophage phenotypes using classic markers, including NOS2 and CD206 11 , 12 , 14 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are conflicting reports regarding changes in the M2 phenotype 10,12,14,15 . Some studies found an enhancement of the M2 phenotype in periodontitis, 10 , 12 whereas other studies found a decrease 14 , 15 . In this context, phenotypic switch of macrophage M1/M2 remains uncertain because of the lack of an in situ analysis of the macrophage phenotypes using classic markers, including NOS2 and CD206 11 , 12 , 14 …”
mentioning
confidence: 99%
“…Clinical and animal studies that used either metabolic markers, 7–11 inflammatory cytokines, 11–13 or cell surface markers 11 , 14 for macrophage phenotyping, both in vivo and in vitro, have consistently suggested an enhanced phenotype and increase in the number of M1‐like macrophages in periodontitis. However, there are conflicting reports regarding changes in the M2 phenotype 10,12,14,15 . Some studies found an enhancement of the M2 phenotype in periodontitis, 10 , 12 whereas other studies found a decrease 14 , 15 .…”
mentioning
confidence: 99%
“…In IL-4, a proinflammatory cytokine is capable of inducing apoptosis of osteoblasts thus contributing to the progression of alveolar bone loss [9] and induces apoptosis in monocytes [17]; three polymorphisms (IL-4 −590 C/T (rs2243250), −33 C/T (rs2070874), and 70-bp) were addressed in a meta-analysis [17], which found, in most studies, no significant association between these genetic variants and the risk of developing periodontitis (Table 1). One of the possible explanations for such results is the potential publication that may have affected the evaluations for the 33-C/T and 70-pb polymorphisms because of the small number of studies for these polymorphisms (seven and four, resp.).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this result, we hypothesised that FXIII is involved in the activation of these cells. Recently, FXIII-A was reported to be a good marker of macrophage alternative pathway activation, but the interaction of coagulation factor FXIII with cells of the immune system has been demonstrated infrequently (Navarrete et al, 2014). This relationship includes the modification of FXIII expression during monocyte differentiation and monocyte-macrophage activation, and is supported by the presence of FXIII in the cytoplasm of monocytes/macrophages with phagocytic potential.…”
Section: Discussionmentioning
confidence: 99%